2015
DOI: 10.4103/1117-6806.162582
|View full text |Cite
|
Sign up to set email alerts
|

Urethroplasty practices among reconstructive urologists in Nigeria

Abstract: Objectives:To determine the national practice patterns in the management of male urethral stricture disease by the open urethroplasty technique.Materials and Methods:A questionnaire-based national survey of Nigerian urologists was performed during the 19th Annual General Meeting and Scientific Conference of the National Association of Urological Surgeons of Nigeria, held at Ibadan, Southwest Nigeria in 2013.Results:A total of 55 respondents (67.1%) completed the questionnaire. About 43.6% were between the ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The proportion of stricture resulting from trauma is higher than strictures from post infective cause (Table 1). This is similar to reported urethral stricture aetiology in the literatures from sub-Saharan Africa [5, 8-10]. The rate of urethral stricture recurrence in this study was 25%, which is similar to that reported by Bello et al [3] which puts the recurrence rate at 27.8%.…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of stricture resulting from trauma is higher than strictures from post infective cause (Table 1). This is similar to reported urethral stricture aetiology in the literatures from sub-Saharan Africa [5, 8-10]. The rate of urethral stricture recurrence in this study was 25%, which is similar to that reported by Bello et al [3] which puts the recurrence rate at 27.8%.…”
Section: Discussionsupporting
confidence: 91%
“…Before then, most of the patients had either urethral dilatation or anastomotic urethroplasty or both, the failed dilatation often preceding the urethroplasty. Dilatation, the first treatment for urethral stricture, is palliative[ 1 ] and similar to direct vision internal urethrotomy[ 29 ] may actually worsen the stricture. [ 3 ] The unit currently reserves dilatation for short-segment urethral stricture occurring concurrently with benign prostatic hyperplasia so that both can be treated at the same operating session.…”
Section: Discussionmentioning
confidence: 99%
“…The urethra measures about 16 to 22 cm in the adult males and 4 cm in the adult females. [ 1 ] In males, it is anatomically divided into posterior and anterior segments. The posterior segment, traditionally referred to as the posterior urethra, measures about 4 cm and traverses the prostate and pelvic membrane beginning at the bladder neck.…”
Section: Introductionmentioning
confidence: 99%
“…The management of the oral wound has been a subject of discussion and opinion varies as to whether the wound should be closed or not. 17 The oral wound was left open and packed with wet gauze in the authors' practice. The maximum duration of packing (compression) in this study was 48 h and thereafter, hexethidine mouth wash 18 was done after each meal.…”
Section: Discussionmentioning
confidence: 99%